Penetration of Ceftaroline into the Epithelial Lining Fluid of Healthy Adult Subjects - Riccobene, Todd A.; Pushkin, Richard; Jandourek, Alena; Knebel, William; Khariton, Tatiana (Antimicrobial agents and chemotherapy, 2016)
Ceftaroline, the active metabolite of the prodrug ceftaroline fosamil, is a cephalosporin with bactericidal activity against Gram-positive organisms, including methicillin-resistant Staphylococcus aureus (MRSA). This study aimed to (i) evaluate ceftaroline concentrations in human plasma and epithelial lining fluid (ELF) and (ii) develop a population pharmacokinetic (PK) model for plasma and ELF to be used in PK/pharmacodynamic (PD) target attainment simulations. Ceftaroline concentrations in ELF and plasma at steady state (day 4) were measured in healthy adult subjects for two dosages: 600 mg every 12 h (q12h) and 600 mg every 8 h (q8h). Both were well tolerated with no serious adverse events. The penetration of free ceftaroline into ELF, assuming 20% protein binding in plasma and no protein binding in ELF, was ≈23%. The population PK model utilized a two-compartment model for both ceftaroline fosamil and ceftaroline. Goodness-of-fit criteria revealed the model was consistent with observed data and no systematic bias remained. At 600 mg q12h and a MIC of 1 mg/liter, 98.1% of simulated patients would be expected to achieve a target free drug concentration above the MIC ( f T>MIC) in plasma of 42%, and in ELF 81.7% would be expected to achieve a target f T>MIC of 17%; at 600 mg q8h, 100% were predicted to achieve an f T>MIC in plasma of 42% and 94.7% to achieve an f T>MIC of 17% in ELF. The literature and data suggest the 600 mg q12h dose is adequate for MICs of ≤1 mg/liter. There is a need for clinical data in patients with MRSA pneumonia and data to correlate PK/PD relationships in ELF with clinical outcomes.